Association between helicobacter pylori infection and body mass index, before and after eradication of infection in hemodialysis batients - Mojgan Jalalzadeh; Mohammad Hassan Ghadiani; Nouraddin Mousavinasab (Society of Diabetic Nephropathy Prevention, 2012)
Background: In dialysis patients, chronic infections have been associated with cachexia and anorexia. Objectives: This study was carried out to determine the association between Helicobacter pylori (HP) infection and body mass index (BMI) in hemodialysis (HD) patients. Patients and Methods: Ninety eight patients were divided into two groups of negative (group 1) and positive (group 2), for HP. BMI of all patients was measured at the beginning and in group2 after six months following eradication of HP. Before dialysis, various paraclinical parameters were checked at the same intervals. Results: Fifty-nine patients were enrolled in group 1 and 39 patients in group 2. The means of BMI in groups 1 and 2 were 23.4±3.7 and 25.8±4.4kg/m², respectively. Prior to the study, there was no significant difference for BMI, duration of HD and paraclinic data between two groups. Group 2 took anti HP therapy and eradication occurred in 30 of them. In this group six months after eradication of HP, the BMI was significantly decreased from 25.02±4.4 to 24.4±4.0 kg/m² (P = 0.001). Also six months following the eradication of HP, the mean of serum albumin level was significantly declined from 4.2 to 3.7 g/L (P<0.001). There was also significant decrease in cholesterol (P=0.001), blood urea nitrogen (P=0.005) and calcium (P=0.02). However, significant increase in hemoglobin level was also seen (P=0.03). Conclusions: The results of this study show that eradication of HP has an impact on BMI. The results need to be investigated with larger cases.